2017
DOI: 10.18632/oncotarget.20105
|View full text |Cite
|
Sign up to set email alerts
|

Metformin ameliorates sepsis-induced brain injury by inhibiting apoptosis, oxidative stress and neuroinflammation via the PI3K/Akt signaling pathway

Abstract: Sepsis-induced brain injuries increase mortality, morbidity, cognitive impairment and lack of effective therapeutic treatment. Previous studies have suggested that metformin provides neuroprotective effects against ischemia, brain trauma and other brain damage, but whether metformin protects a septic brain remains unknown. Thus, the aim of this study is to investigate the possible effects and the mechanism of metformin against septic brain damage using the cecal ligation and puncture (CLP) model. Mice were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 32 publications
3
48
0
1
Order By: Relevance
“…Likewise, in another research, it was revealed that metformin could reduce the concentration of inflammatory marker YKL-40 (33). Metformin also reduces the production of sepsis inflammatory cytokines, produced by neutrophils and monocytes, including IL-6, IL-1β, and TNF-α (34). In an investigation on obese children aged 6 to 12 years, it was found that metformin reduced the level of inflammatory factors such as TNF-α, IL-8 and insulin resistance (35).…”
Section: Metformin and Inflammatory Markersmentioning
confidence: 88%
See 1 more Smart Citation
“…Likewise, in another research, it was revealed that metformin could reduce the concentration of inflammatory marker YKL-40 (33). Metformin also reduces the production of sepsis inflammatory cytokines, produced by neutrophils and monocytes, including IL-6, IL-1β, and TNF-α (34). In an investigation on obese children aged 6 to 12 years, it was found that metformin reduced the level of inflammatory factors such as TNF-α, IL-8 and insulin resistance (35).…”
Section: Metformin and Inflammatory Markersmentioning
confidence: 88%
“…Investigations have indicated that metformin leads to AKT phosphorylation by phosphatidylinositol-3-kinase (PI3K) activation, which this process is involved in maintaining mitochondrial integrity and increasing the ability to cope with damage induced by inflammation and oxidative stress. By inducing the production and increasing the activity of the antioxidant system, such as SOD, metformin cleans the ROS from brain tissue (34,66,67). During the brain ischemia, ROS production increases in tissue.…”
Section: The Antioxidant Role Of Metforminmentioning
confidence: 99%
“…Treatment with different substances containing antioxidants prevented the harmful effects of diabetes mellitus on neurological tissues. In the previous studies [38][39][40] , it has been found that metformin prevents the brain damage by reducing oxidative stress. The results of our study are in line with these studies, and significant prevention of the neuronal tissue damage was found in all areas of the brain of the animals.…”
Section: Discussionmentioning
confidence: 97%
“…Minimization or avoidance of iatrogenic factors related to treatment (e.g., prolonged use of benzodiazepine sedation, and adequate pain treatment) and non‐pharmacological modalities (e.g., physiological light cycle, cognitive stimulation, and early mobilization) may prove useful (Souza‐Dantas et al , ). Existing drugs such as metformin (Tang et al , ) and minocycline (Adembri et al , ) show brain protective effects in experimental sepsis. The natural antioxidant berberine improved survival in a rat CLP model but also motor and cognitive functions (Shi et al , ).…”
Section: Sepsis: a New Who Global Health Prioritymentioning
confidence: 99%